Relationship between C-reactive protein, ferritin serum and cluster of differentiation 4 cell count with pulmonary tuberculosis in naive HIV patient in Bali - Styawan, Ida Bagus Putu Adi; Somia, I Ketut Agus; Candrawati, Ni Wayan; Kusumawardani, Ida Ayu Jasminarti Dwi; Arisanti, Ni Luh Putu Eka; Artana, I Gusti Ngurah Bagus; Rai, Ida Bagus Ngurah (International Journal of Advances in Medicine, 2022)
Background: Diagnostic of Pulmonary tuberculosis (PTB) in patients with Human immunodeficiency virus (HIV) infection remain challenging. Evaluation based on clinical symptoms, inflammation biomarkers, and immunodeficiency status, can provide a feature of PTB disease in HIV patient. The aim of the study was to analyze the relationship between acute phase reactant and immunodeficiency status with PTB in patients with naïve HIV infection. Methods: A cross sectional study was conducted in Sanglah General Hospital and Kuta Selatan Public Health Service on February-June 2021. C-reactive protein (CRP), Ferritin serum levels, and CD-4 cell count were obtained from patient’s serum. Data were collected by questionnaire. Bivariate analysis using Chi square test or Kolmogorov Smirnov test, and multivariate analysis using logistic regression. Results: A total of 60 participants were included in this study, and 58.3% had pulmonary tuberculosis (38.3% bacteriologically confirmed, 20% clinically confirmed). Fifty five percent participants had CRP level ≥10 mg/l, 83% had ferritin serum level ≥260 ng/ml, and 83% had CD4 cell count<200 cell/ml. Multivariate analysis showed that the most influential factor for PTB in HIV patients was CRP level≥10 mg/l (adjusted prevalence ratio/APR=4.9; 95%CI=7.81-2327,04, p=0.001) and ferritin serum level ≥260 ng/ml (APR=3.32, 95%CI=1.752-433.65, p=0.018). Conclusions: High CRP and ferritin serum levels were significantly related with PTB in naive HIV patients. No relationship was found between low CD4 cell count and PTB in naive HIV patients.